2018
DOI: 10.17521/cjpe.2018.0121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of desertification on the C:N:P stoichiometry of soil, microbes, and extracellular enzymes in a desert grassland

Abstract: Aims In order to discuss the underlying mechanism of desertification effect on the ecological stoichiometry of soil, microbes and extracellular enzymes, we studied the changes of soil, soil microbial and extracellular enzyme C:N:P stoichiometry during the desertification process in the desert grassland in Yanchi County, China. MethodsThe "space-for-time" method was used. Important findings The results demonstrated that: (1) Soil C, N, P contents and soil C:P, N:P significantly decreased, but soil C:N gradually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…The functional groups of legumes affected the contents of C and N in soil, and the changes in nitrogen fixation and community composition affected the absorption and transformation of C and N in soil (Hooper and Vitousek, 1998 ; Spehn et al, 2002 ). The results showed that the increase in the legume functional group not only affected the diversity of community species but also reduced the loss of soil C and N in the alpine desert grassland (Wen et al, 2013 ; Wu et al, 2018 ). The results indicate that different PFGs would adapt to the changes in the external environment according to their own traits under the same resource environment.…”
Section: Discussionmentioning
confidence: 99%
“…The functional groups of legumes affected the contents of C and N in soil, and the changes in nitrogen fixation and community composition affected the absorption and transformation of C and N in soil (Hooper and Vitousek, 1998 ; Spehn et al, 2002 ). The results showed that the increase in the legume functional group not only affected the diversity of community species but also reduced the loss of soil C and N in the alpine desert grassland (Wen et al, 2013 ; Wu et al, 2018 ). The results indicate that different PFGs would adapt to the changes in the external environment according to their own traits under the same resource environment.…”
Section: Discussionmentioning
confidence: 99%
“…(Hooper and Vitousek, 1998;Spehn et al, 2002). In the alpine desert grassland, the increase of legumes function group not only affected the diversity of community species, but also reduced the loss of soil C and N (Wen et al, 2013;Wu et al, 2018). The results indicated that different plant functional groups would adapt to the changes of external environment according to their own traits under the same resource environment.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively poor N in soil limited the MBN fixation. Meanwhile, plants increased investment to P-rich ribosomal RNA in P-rich soil environments [18], resulting in the low N:P ratio (Figure 2).…”
Section: Soil Microbial Properties and Stoichiometry Of Z Planispinum...mentioning
confidence: 99%
“…Other scholars [16,17] proposed that the theory of extracellular enzyme stoichiometry can clarify the balance between microbial biomass stoichiometry and soil element composition. Wu et al [18] clarified that there is a strong covariant relationship between soil, microorganisms, and extracellular enzyme stoichiometry. In conclusion, forest soil stoichiometry emphasizes the correlation between soil elements, microorganisms, and extracellular enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation